Law Enforcement Patterns Against Radical Groups in Denpasar City - I Made Wira Bhawa; Ni Gusti Agung Ayu Mas Tri Wulandari; I Gede Agus Kurniawan (Dinasti Research, 2025)
The purpose of this study is to determine the description of the appropriate law enforcement pattern to be implemented by the Denpasar City Government in overcoming the spread of radicalism or radicalism. Activities to overcome radicalism in Indonesia are regulated in Presidential Regulation Number 7 of 2021 concerningNational Action Plan for the Prevention and Handling of Violent Extremism Leading to Terrorism 2020-2024. The formulation of the problem in this study is: what factors hinder the Denpasar City Government in overcoming the spread of radicalism and what is the role and appropriate enforcement pattern to be implemented by the Denpasar City Government to overcome the spread of radicalism. This study uses empirical legal research methods and descriptive qualitative data analysis. The resolution of the factors that hinder the Denpasar City Government in overcoming radicalism in Denpasar City, namely: weak regulatory or regulatory factors, lack of synergy between institutions and budget constraints, then the appropriate law enforcement pattern to be implemented by the Denpasar City Government in overcoming the spread of radicalism, namely: preventive patterns, repressive patterns and also deradicalization.